Retrenchment Policy and Procedure : An Exploratory Study on the Awareness of Employees - Hapriza Ashari, author 376304; Universiti Teknologi Malaysia. Fakulti Pengurusan dan Pembangunan Sumber Manusia 2478; Universiti Teknologi Malaysia. Pusat Pengurusan Penyelidikan 520 (Skudai, Johor : Penerbit UTM, 2006)
Includes bibliographical references.